Image of Mahishasuramardini in the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The sanctum of the temple has a sculpture of Mahishasuramardini sculpture. The multi-armed Goddess is shown slaying Mahisha (the buffalo demon), who is depicted in zoomorphic form. Presently, her head and arms are broken. She is accompanied by a few figures who are also seen killing asuras (demons). Her vahana (mount) is also depicted.